Negative pressure wound therapy in complex cranio‐maxillofacial and cervical wounds. Issue 1 (23rd November 2017) - Novelli, Giorgio; Daleffe, Francesco; Birra, Gisella; Canzi, Gabriele; Mazzoleni, Fabio; Boni, Pietro; Maino, Clara; Giussani, Carlo; Sozzi, Davide; Bozzetti, Alberto
Abstract: The care and the management of the healing of difficult wounds at the level of the skull‐facial face many problems related to patient compliance and the need to perform multiple dressings, with long periods of healing and, occasionally, a very long hospitalisation period. The introduction and evolution of negative pressure wound therapy (NPWT) in the treatment of difficult wounds has resulted in better healing, with a drastic reduction in terms of time and biological costs to the patient and cost to the health care system. The main aim of this study is to describe and discuss, using out our experience, the usefulness of NPWT in the cranial‐facial‐cervical region. We studied 16 patients with complex wounds of the cranial‐facial‐cervical region treated with NPWT. We divided clinical cases in four groups: cervicofacial infectious disease, healing complications in oncological‐reconstructive surgery, healing complications of injury with exposure of bone and/or internal fixations and healing complications in traumatic injury with loss of substance. We evaluated complete or incomplete wound healing; application time, related also to hospitalisation time; days of intensive care unit (ICU) stay; management of the upper airways; timing of medication renewal; and patient comfort and compliance (on a scale of 1–5). Depression values were always between −75 and −125 mmHg in a continuous aspiration pattern. For every patient, we used the ActiVAC Therapy Unit, derived from the vacuum‐assisted closure system (Kinetic Concepts Inc., San Antonio, TX). Medication renewals were performed every 48–72 hours. The NPWT application time ranged from 4 to 22 days (mean of 11·57 day). Therapy was effective to gain a complete restitutio ad integrum in every patient included in the group of cervicofacial infectious disease. Therapy has, however, been well tolerated in our series; this is probably due to the decreased number of applications, the ease of use and the comfort of the system relative to traditional dressing. Results were satisfactory for most of cases treated; faster and more effective wound healing was achieved. The lower number of NPWT applications, relating to standard dressings, led to an increase in patient comfort and compliance and a decrease in the use of medical, and in some cases economic, resources according to international literature.